2006
DOI: 10.1002/chem.200500834
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic and Kinetic Study of the Formation of Metal Nanoparticles by Using Synthetic Tyrosine‐Based Oligopeptides

Abstract: Synthetic oligopeptides containing redox-active tyrosine residues have been employed to prepare gold and silver nanoparticles. In this reduction process an electron from the tyrosinate ion of the peptide is transferred to the metal ion at basic pH through the formation of a tyrosyl radical, which is eventually converted to its dityrosine form during the reaction. This reaction mechanism was confirmed from UV-visible, fluorescence, and EPR spectroscopy and was found to be pH-dependent. Transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 37 publications
6
141
0
1
Order By: Relevance
“…However, a strong fluorescence band was observed at 400 nm, which indicated the formation of dityrosine [47][48][49] as a result of a redox reaction between Au III and tyrosine (dityrosine was not detected if HAuCl 4 was not added to the amino acid mixtures). One can find this intriguing since cysteine and methionine can form highly stable complexes with gold, limiting the reducibility of Au III in the case of tryptophan [26].…”
Section: Preparation Of Auqcs With Peptidesmentioning
confidence: 99%
“…However, a strong fluorescence band was observed at 400 nm, which indicated the formation of dityrosine [47][48][49] as a result of a redox reaction between Au III and tyrosine (dityrosine was not detected if HAuCl 4 was not added to the amino acid mixtures). One can find this intriguing since cysteine and methionine can form highly stable complexes with gold, limiting the reducibility of Au III in the case of tryptophan [26].…”
Section: Preparation Of Auqcs With Peptidesmentioning
confidence: 99%
“…This is probably because the reduction ability of tyrosine in trypsin is activated with the alkaline pH. 22,27 Recently, Tan et al have also investigated the amino-acid sequence in peptides for the synthesis of peptide-stabilized Au NPs. 34 It was found that tyrosine and tryptophan showed fairly gold reduction ability of AuCl4 -when present in the peptide sequence.…”
Section: Trypsin-stabilized Fluorescence Au Ncs With a Red Emissionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Recently, there has been increasing interest in the development of biological synthesis for Au NPs because of the need for an environmentally acceptable solvent system and eco-friendly reducing and capping agents. [26][27][28] Xie et al first demonstrated the synthesis of highly fluorescent protein-stabilized Au NCs using a bovine-serum alubumin (BSA)-templated method. 22 The as-prepared Au NCs consisted of 25 gold atoms (Au25) with a red emission at 640 nm.…”
Section: Introductionmentioning
confidence: 99%
“…This is unlike earlier examples where the peptides are mostly oxidized during particle formation and could therefore not be reused. 11,13,45 Here, the peptide can be separated from the colloidal silver by dissolution of the composite in methanol. After centrifugation and solvent evaporation, the peptide can be recovered.…”
Section: Potential Of the Approachmentioning
confidence: 99%